2021
DOI: 10.1097/j.jcrs.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Five-year long-term outcomes of intrastromal corneal ring segment implantation using the manual technique for keratoconus management

Abstract: This retrospective study of 124 eyes concluded that ICRS implantation was a stable, safe, and effective procedure for keratoconus management over a 5-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…No regression was observed in any visual or topographic parameter during the entire follow-up. Regarding the subgroup analysis, both younger and older patients demonstrated similar and stable results from preoperative to the 5-year visit, except for the minimal change in pachymetry value over time [21].…”
Section: Mednext Journal Of Medical and Health Sciencesmentioning
confidence: 78%
“…No regression was observed in any visual or topographic parameter during the entire follow-up. Regarding the subgroup analysis, both younger and older patients demonstrated similar and stable results from preoperative to the 5-year visit, except for the minimal change in pachymetry value over time [21].…”
Section: Mednext Journal Of Medical and Health Sciencesmentioning
confidence: 78%
“…5,6 Intrastromal corneal ring segments (ICRS) can decrease irregular astigmatism and corneal higher-order aberrations (HOA), thus improving VA, refraction and keratometry. 7,8 Although the long-term stability of ICRS implantation and its ability to halt the disease progression has been recently described, 9,10 it remains a point of controversy. 11 Recent publications have confirmed the efficacy and safety of different treatment combinations: CXL with excimer corneal ablation, [12][13][14] and ICRS with CXL.…”
Section: Introductionmentioning
confidence: 99%
“…(2) There have been numerous studies (3)(4)(5)(6)(7)(8)(9) confirming the safety and efficacy of Ferrara ICRS implants (AJL, Ophthalmic, Spain) in patients with keratoconus, but few have analyzed the procedure's stability in the short, medium and long term. Most of the studies (10)(11)(12)(13)(14)(15)(16)(17) have reported a maximum follow-up of 5 years, showing evidence of improved visual, refractive, and topographical quality. A number of these studies (11,13,15,17) have concluded that this improvement remains stable at 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies (10)(11)(12)(13)(14)(15)(16)(17) have reported a maximum follow-up of 5 years, showing evidence of improved visual, refractive, and topographical quality. A number of these studies (11,13,15,17) have concluded that this improvement remains stable at 5 years. The study by De Araujo et al (14) corroborated the efficacy of ICRS, but its effect did not remain stable for patients younger than 21 years old.…”
Section: Introductionmentioning
confidence: 99%